2018
DOI: 10.1183/13993003.01611-2016
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age at delivery, lung function and asthma in offspring: a population-based survey

Abstract: There is limited information about potential impact of maternal age on the respiratory health of offspring. We investigated the association of maternal age at delivery with adult offspring's lung function, respiratory symptoms and asthma, and potential differences according to offspring sex.10 692 adults from 13 countries participating in the European Community Respiratory Health Survey (ECRHS) II responded to standardised interviews and provided lung function measurements and serum for IgE measurements at age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 42 publications
4
18
2
1
Order By: Relevance
“…Interestingly, we noted that a high maternal age at delivery was a protective factor for asthma in this study. Similar to our finding, one recently published large-scale study, investigating 10,692 adults from 13 European countries, reported that increasing maternal age at delivery was associated with increasing forced expiratory volume in 1 s (FEV 1 ) and a low incidence of asthma at age 25–55 years, and the inverse correlation between maternal age at delivery and incident asthma mainly existed in females [31]. Additionally, we speculated that environmental factors as the aforementioned discussion regarding sibling effect on asthma might also at least partly explain the inverse association between maternal age at delivery and incident childhood asthma.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, we noted that a high maternal age at delivery was a protective factor for asthma in this study. Similar to our finding, one recently published large-scale study, investigating 10,692 adults from 13 European countries, reported that increasing maternal age at delivery was associated with increasing forced expiratory volume in 1 s (FEV 1 ) and a low incidence of asthma at age 25–55 years, and the inverse correlation between maternal age at delivery and incident asthma mainly existed in females [31]. Additionally, we speculated that environmental factors as the aforementioned discussion regarding sibling effect on asthma might also at least partly explain the inverse association between maternal age at delivery and incident childhood asthma.…”
Section: Discussionsupporting
confidence: 90%
“…For example, in the present study, the time spent for outdoor exercise was significantly higher in males (7.9 ± 7.6 hours) than that in females (7.3 ± 7.9 hours), which, due to time‐activity patterns, may affect the lung function development. However, some other studies found that males were more vulnerable to environmental factors . Therefore, the effects of genders as a modifier on the association between home renovation exposure and lung function are still unclear, and further studies are required to determine the cause of such differences.…”
Section: Discussionmentioning
confidence: 97%
“…As for immune-mediated diseases, previous studies have indicated associations with increasing maternal age at delivery with an increased risk for type 1 diabetes [13] and food allergies [14] in the offspring. A fine-tuned balance between genetic, immunological, metabolic, and hormonal factors is necessary for reproduction, and all of these factors are likely involved in the aging process [15]. Therefore, maternal aging may affect health outcomes in offspring, including with regard to the development of their immune response.…”
Section: Discussionmentioning
confidence: 99%